New hybrid biopolymer based on CMC/kappa-carrageenan for application as electrolyte system - Siti Zulaikha, Md Jamil (2017)
Today, the uses of electrochemical devices such as cellphone are having safety issue due to the exploitation of the battery which is harmful to the user. The uses of biodegradable material in electrolyte system can enhance the performance of devices and also bring to the green technology. This research reports on the biopolymer electrolyte was produced using Carboxymethyl cellulose (CMC) and kappa-carrageenan (KC) by hybrid method. This research was divided into 3 phases which are sample preparation, samples characterization and data analysis. The hybrid CMC/KC solid biopolymer electrolytes (SBEs) with different percentage were prepared by solution casting technique. The transparent and colorless with no phase separation biopolymer electrolytes were obtained. Then, the characterization of samples were done by using Fourier Transform Infrared Spectroscopy (FTIR), X-rays Diffractometer (XRD) and Electrical Impedance Spectroscopy (EIS). The characterization was divided into two sections which were structural characterization by using FTIR and XRD, and electrical measurement by using EIS. FTIR characterization shows some shifted wavenumber and increase intensity of peak due to hybrid biopolymer electrolytes complexes between CMC and KC. In addition, there are disappear of peak when introducing which clearly shown the interaction between CMC and KC which are affect the ionic conductivity measurement of hybrid SBEs system. XRD result shown that there are increasing broadness of peak as increasing the percentage of KC in the hybrid biopolymer electrolyte. In EIS measurement, the hybrid biopolymer electrolyte of 40/60 percentage of CMC/KC shows the highest conductivity at room temperature was 9.07×10-6 Scm-1.The regression value R2 was found close to unity. From this observation, it revealed that the temperature relationship of SBEs system obey Arrhenius rule. The conductivity behaviour of biopolymer electrolytes was analysed by dielectric studies by measure the dielectric constant and dielectric loss.